ANALYSIS OF THE INFLUENCE OF THE LENGTH OF THE CONTRAILER ROUTE ON THE EQUIVALENT DISTANCE OF CARGO DELIVERY - Денис, Елена (SWorldJournal, 2020)
analysis of the impact of the length of the piggyback route on cargo delivery.